2022
DOI: 10.1093/treephys/tpac029
|View full text |Cite
|
Sign up to set email alerts
|

Aridity and cold temperatures drive divergent adjustments of European beech xylem anatomy, hydraulics and leaf physiological traits

Abstract: Understanding plant trait coordination and variance across climatic gradients is critical for assessing forests’ adaptive potential to climate change. We measured eleven hydraulic, anatomical and leaf-level physiological traits in European beech (Fagus sylvatica L.) along a moisture and temperature gradient in the French Alps. We assessed how traits covaried, and how their population-level variances shifted along the gradient. The intrapopulation variances of vessel size and xylem-specific conductivity reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 103 publications
2
4
1
Order By: Relevance
“…Therefore, the populations sampled in our study area represent a valuable genetic pool that can be exploited in forest management planning; 2. the measured turgor loss point (i.e., a proxy of drought resistance) was similar to or even less negative than values recorded in adult trees growing in central and northern Europe [31,32]. Likewise, measured xylem anatomical traits, such as mean conduit diameter (a proxy of xylem embolism vulnerability), were similar to values recorded in European beech growing in the warmer and more arid sites of central Europe [4,33,34]. Moreover, in the Mediterranean region, F. sylvatica grows in sites with specific microclimatic conditions (i.e., growing season rainfall not lower than about 400 mm and VPD not higher than about 3 kPa).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, the populations sampled in our study area represent a valuable genetic pool that can be exploited in forest management planning; 2. the measured turgor loss point (i.e., a proxy of drought resistance) was similar to or even less negative than values recorded in adult trees growing in central and northern Europe [31,32]. Likewise, measured xylem anatomical traits, such as mean conduit diameter (a proxy of xylem embolism vulnerability), were similar to values recorded in European beech growing in the warmer and more arid sites of central Europe [4,33,34]. Moreover, in the Mediterranean region, F. sylvatica grows in sites with specific microclimatic conditions (i.e., growing season rainfall not lower than about 400 mm and VPD not higher than about 3 kPa).…”
Section: Discussionsupporting
confidence: 75%
“…actually experienced, in 2022, a more severe hot and drought-like summer than in the past compared to the other two study sites. However, it can be noted that plants growing in this site showed a D value of about 20 µm, similar to value recorded in F. sylvatica trees growing in the more xeric and warmer sites of central Europe [33,34]. At a higher altitude study site, F. sylvatica trees also showed a lower solitary vessel index and higher values of vessel grouping index and vessel multiple vessel fraction values than those recorded in plants growing at lower altitudes.…”
Section: Phenotypic Plasticity Of Beech Populations At Its Southern D...supporting
confidence: 79%
See 1 more Smart Citation
“…The results of the current study revealed that, during different periods of dormancy, the vessel density in the xylem of HF was significantly higher than that in the xylem of CF, and the vessel area of HF was significantly smaller than that of CF (Figure 4, Table 1). Therefore, the narrowing of vessels and the increase in vessel density of trees in cold environments are adaptive mechanisms to survive in low temperature stress environments [73,74]. Based on the study data, HF exhibits a reduced risk of embolism caused by severe winter temperatures or alternating high and low temperatures in early spring, and thus, it displays greater resistance to low temperatures.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, high temperatures impacted the respiration, transpiration and photosynthetic rates of Populus euphratica [47], thereby limiting its growth. In this study, the sensitive minimum temperature for the changes in the component parameters of the xylem of Populus euphratica was found to be 16.1 • C. Low temperatures also affected the metabolic processes and enzyme activities of Populus euphratica to varying degrees, leading to stomatal closure and impacting respiration, photosynthesis and other physiological functions [50], which, in turn, affects its growth. When the water table is too low, the reduced evaporation and photosynthesis capacity in a low-temperature environment weaken photosynthesis and respiration, hindering the normal growth of Populus euphratica.…”
Section: Anatomical Characteristics Of Populus Euphratica Xylem In Re...mentioning
confidence: 71%